History from the Howdah: A New Methodology for Animal History: Review of Susan Nance, Entertaining Elephants: Animal Agency and the Business of the American Circus - Vandersommers, Daniel (Humanimalia, 2014)
Susan Nance, Entertaining Elephants: Animal Agency and the Business of the American Circus. Baltimore: The Johns Hopkins University Press, 2013. 294 pp. 55.00 hb.